The Social Exclusion of Homeless Menstruators within the Sanitary Dignity Framework and its Implementation - Ramafalo, Katleho (Department of Public Law, 2022)
The Sanitary Dignity Framework (2019) is a policy that aims to preserve and maintain indigent girls' and women's dignity during menstruation. In South Africa, the term “sanitary dignity”, can be equated to what the rest of the world recognizes as menstrual hygiene management (MHM). Sanitary dignity or MHM is centred around the provision of menstrual health hygiene products (MHPs) such as tampons and sanitary pads to anyone who menstruates and cannot afford to purchase MHPs for themselves. Limited of access to MHPs, water and sanitation facilities, and privacy make it impossible for vulnerable menstruators to achieve sanitary dignity. This policy excludes street-based homeless menstruators as it only makes provisions for those who have access to state-funded institutions such as; quintile 1, 2, and 3 schools, mental institutions, hostels, places of care, and prisons. Street-based homeless menstruators are marginalized twofold; they reside on the streets and they menstruate. This dissertation discusses how the social exclusion of street-based homeless menstruators within the Sanitary Dignity Framework strips them of their fundamental right to dignity by denying them access to the sanitary dignity they are entitled to.